AKTUALISASI DAN ALIENASI DIRI DALAM KERJA - Batlayeri, Willem (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2022)
The study of self-actualization and alienation is study of cultural studies. Theconcept of self-actualization and alienation confirms Marx's thinking about the labor theory of value. On the one hand, work is understood as human self- actualization, the fullness of human potential, and as a form of social solidarity. On the other hand, work raises the problem of self-alienation. That is, when people prioritize the value of production without being extracted, humans are alienated from them and from their own work. Humans work solely to maintain their lives and to fulfill their needs. Work is no longer meant to self-actualize, but works solely for the benefit of the capitalists. Keywords: Work, Self Actualization, Self Alienation, Capitalism, Dehumanization